2018
DOI: 10.1101/314708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sperm morphology differences associated with pig fertility

Abstract: 27Artificial insemination is routinely used in commercial pig breeding, for which the use of high quality 28 semen samples is imperative. Currently, semen quality is determined manually by morphological 29 assessment. This method leads to high inter-operator variability due to its subjective nature. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In the current study, boars with varicocele had smaller average sperm head area than boars without varicocele. A recent study published by Mandawala et al, (2018) reported that higher mean nucleus area in boars, which is a function of greater head width and lower variability between sperm cell heads, positively influenced fertility. Previous work by Rempel et al, (2019) identified that boars with reduced head shape from spring to summer subsequently had reduced fertility rates in comparison to boars with similar head shape at spring or summer collections.…”
Section: Discussionmentioning
confidence: 98%
“…In the current study, boars with varicocele had smaller average sperm head area than boars without varicocele. A recent study published by Mandawala et al, (2018) reported that higher mean nucleus area in boars, which is a function of greater head width and lower variability between sperm cell heads, positively influenced fertility. Previous work by Rempel et al, (2019) identified that boars with reduced head shape from spring to summer subsequently had reduced fertility rates in comparison to boars with similar head shape at spring or summer collections.…”
Section: Discussionmentioning
confidence: 98%
“…Contrastingly, according to Hirai et al (19) the sperm heads of highly fertile boars were less elongated and significantly smaller than those of less fertile boars. Mandawala et al (27), who identified three categories of morphological sperm head in boars, suggested that a certain type may be predominant in semen from subfertile boars. Curry (11) also indicated that certain subtle differences in the shape of the sperm head may affect the fertility potential of the sperm.…”
Section: Discussionmentioning
confidence: 99%
“…We present a novel tool for nuclear morphometry, which quantitatively measures a range of nuclear and sub-nuclear size and shape parameters. While we have chosen mouse sperm to demonstrate the software, the analysis steps will work on many symmetric or asymmetric shapes of nuclei including, but not limited to sperm from other species [35].…”
Section: Discussionmentioning
confidence: 99%